Barriers to Digital Transformation Implementation in Operations and Supply Chain Management: A Systematic Literature Review (SLR) - Nur Azmi Inayah; Imam Baihaqi (International Journal of Business and Management Technology in Society, 2024)
Purpose – This study seeks to identify and summarize the principal barriers to the implementation of digital transformation in operations and supply chains. Methodology – This research utilizes a Systematic Literature Review (SLR) methodology in accordance with PRISMA criteria. A thorough literature search was performed utilizing the Google Scholar database, concentrating on peer-reviewed articles released from 2019 to 2024. Studies were evaluated according to established inclusion and exclusion criteria. From the initial collection of discovered papers, 20 studies were chosen and examined to systematically discern reoccurring themes and categories of obstacles to digital transformation. Findings – The analysis indicates that digital transformation in operations and supply chain management is obstructed by several significant barriers, including inadequate digital capabilities, resistance to organizational change, interoperability challenges, insufficient infrastructure readiness, and cybersecurity issues. These obstacles diminish operational efficiency, disrupt process integration, and undermine supply chain resilience, thereby restricting the potential advantages of digital transformation programs. Originality – This study enhances the literature by offering a systematic synthesis of challenges to digital transformation in operations and supply chain environments. The study consolidates fragmented information, emphasizing notable research gaps about the varying effects of different barriers on the efficacy of digital transformation. The findings provide significant insights for scholars and practitioners, indicating pathways for future study aimed at creating comprehensive frameworks for evaluating and alleviating impediments to digital transformation.